The Influence of Managerial Involvement in Corporate Social Responsibility on Real Earnings Management Decisions - Hale, Kevin (Journal of business ethics, 2026)
Prior research indicates that a strong commitment to corporate social responsibility (CSR) initiatives can lead to positive firm outcomes. Yet, managers’ levels of involvement in these CSR initiatives are known to vary, with the primary CSR decision-making power either coming from specific firm units (e.g., sustainability committees) or from a broader group of individuals within the firm, depending on firm governance structure. Leveraging psychological ownership and moral consistency literature streams, we predict that the level of managerial involvement in the decision-making process behind company CSR performance will influence a subsequent real earnings management (REM) decision—a decision with inherent ethical tradeoffs. While we document that managers of companies with stronger (weaker) CSR performance are less (more) likely to engage in REM, we expect and find this association to be moderated by managers’ involvement in their company’s CSR decision-making process. Only when managers have decision-making authority related to the relevant CSR initiatives of their company does the accompanying weaker (stronger) CSR performance influence managers’ greater (lesser) propensity to engage in REM. Additional analyses indicate that managers responsible for stronger CSR performance report heightened moral emotions than those responsible for weaker CSR performance. Additional analyses also indicate that our main results are concentrated in a subset of managers with favorable measured perceptions of CSR. Our findings contribute to research on decision-making regarding CSR and REM and highlight practical implications of managerial involvement in CSR initiatives, while also informing psychology research on moral behavior.